On ideals and contraideals in Leibniz algebras - Kurdachenko, L.A.; Subbotin, I.Ya.; Yashchuk, V.S. (Доповіді НАН України, 2020)
A subalgebra S of a Leibniz algebra L is called a contraideal, if an ideal, generated by S coincides with L. We study the Leibniz algebras, whose subalgebras are either an ideal or a contraideal. Let L be an algebra over a field F with the binary operations + and [ , ]. Then L is called a Leibniz algebra (more precisely, a left Leibniz algebra), if it satisfies the following identity: [[a, b], c] = [a, [b, c]] – [b, [a, c]] for all a, b, c ∈ L. We will also use another form of this identity: [a, [b, c]] = [[a, b], c] + [b, [a, c]]. Leibniz algebras are generalizations of Lie algebras. As usual, a subspace A of a Leibniz algebra L is called a subalgebra, if [x,y] ∈ A for all elements x, y ∈ A. A subalgebra A is called a left (respectively right) ideal of L, if [y,x] ∈ A (respectively, [x,y] ∈ A) for every x ∈ A, y ∈ L. In other words, if A is a left (respectively, right) ideal, then [L, A] ≤ A (respectively, [A, L] ≤ A). A subalgebra A of L is called an ideal of L (more precisely, a twosided ideal), if it is both a left ideal and a right ideal, that is, [y, x], [x, y] ∈ A for every x ∈ A, y∈ L. A subalgebra A of L is called an contraideal of L, if Aᶫ = L. The theory of Leibniz algebras has been developed quite intensively, but very uneven. However, there are problems natural for any algebraic structure that were not previously considered for Leibniz algebras. We have received a complete description of the Leibniz algebras, which are not Lie algebras, whose subalgebras are an ideal or a contraideal. We also obtain a description of Lie algebras, whose subalgebras are ideals or contraideals up to simple Lie algebras. Підалгебра S алгебри Лейбніца L називається контраідеалом, якщо ідеал, породжений S, збігається з L. Вивчено алгебри Лейбніца, підалгебри яких є або ідеалом, або контраідеалом. Нехай L алгебра над полем F з бінарними операціями і [ , ]. Тоді L називається алгеброю Лейбніца (точніше, лівою алгеброю Лейбніца), якщо вона задовольняє тотожність [[a, b], c] = [a, [b, c]] [b, [a, c]] для всіх a, b, c∈L. Також використано іншу форму цієї тотожності: [a, [b, c]] = [[a, b], c] [b, [a, c]]. Алгебри Лейбніца є узагальненням алгебр Лі. Підпростір A алгебри Лейбніца L називається підалгеброю, якщо [x,y] О A для всіх елементів x, y∈A. Підалгебра A називається лівим (відповідно правим) ідеалом L, якщо [y, x]∈A (відповідно [x, y]∈A) для всіх x∈A, y∈L. Іншими словами, якщо A є лівим (відповідно правим) ідеалом, то [L, A] ≤ A) (відповідно [A, L] ∈ A ). Підалгебра A із L називається ідеалом L (точніше, двостороннім ідеалом), якщо вона одночасно є лівим і правим ідеалом так, що [x, y], [y, x]∈A для всіх x∈A, y∈L. Підалгебра A із L називається контраідеалом L, якщо AL = L. Теорія алгебр Лейбніца розвивається досить інтенсивно, проте дуже нерівномірно. Однак існують природні для будь-яких алгебраїчних структур задачі, що раніше не розглядалися для алгебр Лейбніца. Отримано повний опис алгебр Лейбніца, які не є алгебрами Лі, підалгебри яких є ідеалом або контраідеалом. Також отримано опис алгебр Лі, всі підалгебри яких є ідеалами або контраідеалами, з точністю до простих алгебр Лі. Подалгебра S алгебры Лейбница L называется контраидеалом, если идеал, порожденный S, совпадает с L. Изучены алгебры Лейбница, подалгебры которых являются либо идеалом, либо контраидеалом. Пусть L алгебра над полем F з бинарными операциями + і [ , ]. Тогда L называется алгеброй Лейбница (точнее, левой алгеброй Лейбница), если она удовлетворяет тождеству [[a, b], c] = [a, [b, c]] [b, [a, c]] для всех a, b, c∈L. Также использована другая форма этого тождества: [a, [b, c]] = [[a, b], c] + [b, [a, c]]. Алгебры Лейбница являются обобщением алгебры Ли. Подпространство A алгебры Лейбница L называется подалгеброй, если [x,y]∈A для всех элементов x, y∈A. Подалгебра A называется левым (соответственно правым) идеалом L, если [y, x]∈A (соответственно [x, y]∈A) для всех x∈A, y∈L. Другими словами, если A является левым (соответственно правым) идеалом, то [L, A] ∈ A (соответственно [L, A] ≤ A). Подалгебра A с L называется идеалом L (точнее, двусторонним идеалом), если она одновременно является левым и правым идеалом так, что [x, y], [y, x]∈A для всех x∈A, y∈L. Подалгебра A с L называется контраидеалом L, если AL = L. Теория алгебр Лейбница развивается достаточно интенсивно, но очень неравномерно. Тем не менее существуют естественные для любых алгебраических структур задачи, которые раньше не рассматривались для алгебр Лейбница. Получено полное описание алгебр Лейбница, которые не являются алгебрами Ли, подалгебры которых являются либо идеалом, либо контраидеалом. Также получено описание алгебры Ли, все подалгебры которых являются идеалами или контраидеалами, с точностью до простых алгебр Ли.